Protest, social movements, and global democracy since 2011 new perspectives - Davies, Thomas; Ryan, Holly Eva.; Pen<U+0303>a, Alejandro Milci<U+0301>ades. (Bingley, U.K. : Emerald, 2016)
In light of the limited achievements of the Arab Spring and other pro-democracy movements, volume 39 examines and unpacks arguments that these protests represent both a new phase and new prospects for democratic mobilization. The volume engages with new theoretical and methodological perspectives and illuminates novel aspects of transnational social movement dynamics, such as the evolving role of information technology, deterritorialisation and government counter-responses.
Protest, social movements and global democracy since 2011 : new perspectives / Thomas Davies, Holly Eva Ryan, Alejandro Milci<U+0301>ades Pen<U+0303>a -- Do issues matter? Anti-austerity protests composition, values, and action repertoires compared / Maria T. Grasso, Marco Giugni, -- Occupying organization : space as organizational resource in Occupy Wall Street / Gianmarco Savio -- Protest and recognition in the Bulgarian summer 2013 movement / Delia Hallberg, Marinus Ossewaarde -- Challenging the gospel of neoliberalism? Civil society opposition to mining in Armenia / Armine Ishkanian -- Transnational resistance networks : new prospects for democratic mobilisation? The Lyon-Turin rail project and the No TAV movement / Lisa Ariemma, Judith Burnside-Lawry -- When social movements become a democratising force : the political impact of the student movement in Chile / Sofia Donoso -- Religion and political activism in post-revolutionary Tunisia / Anna Grasso -- Anarchy or utopia? Turkish media representation of the Gezi Park protests / Zeynep Cihan Koca-Helvaci -- Saudi intervention, sectarianism, and de-democratisation in Bahrain's uprising / Marc Owen Jones.
Print version record
Keywords: Social Science -- Demography; Demonstrations & protest movements; Protest movements; Social movements